Competition Analysis of Imported and Local Oranges - Dini Maulida Rachmi; Rita Nurmalina; Amzul Rifin (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Indonesia is faced by global competition, in particular for its fruit commodity. Orange a commodity currently prioritized to be developed. The availability of seasonal oranges provides an opportunity for the imported orange products to substitute the local oranges. The objective of this study was to analyze the competition between the local oranges and imported oranges. The analytical method used was Almost Ideal Demand System (AIDS). The results show that the local oranges can compete with the imported oranges from China. It is indicated by the positive cross elasticity value (substitution). The decline in the price of oranges imported from China will reduce the market share of local oranges in Indonesia. Therefore, Indonesia needs to improve the marketing efficiency of its local oranges and increases the local orange production to meet its consumption needs of oranges.